Infusing Storytelling and Game Elements in Designing Instructional Media - Salsabila, Firyal Rizki; Maureen, Irena (Proceeding Series of International Conference on Arts and Humanities, 2022)
Storytelling and games have been utilized successfully in education to increase involvement and engagement. However, according to recent research, storytelling and games are not always appropriate to integrate into an instructional setting. Although considered enjoyable, it is not always evident how a storytelling session or game may help students learn or how it can be utilized in a class. The approach was used in creating the Savior of the Kingdom Plantae game, which assists in the learning of middle school Biology. In an ADDIE model, we used the 5/10 approach in the (analyze) design process of the instructional media. To gather more input in this exploratory study, we asked an expert in educational media design and five middle school students to try on the first version of the instructional media. The result from the expert and students showed a good remark during the validation level for both the story elements and the game elements in the media. All in all, as an initial project, the media design is considered good to be developed further.